Phosphate Adsorption in Aridisols in Relation to Soil Properties - Tripathi, K P; Kuamr, Praveen (Annals of Arid Zone, 2016)
Six representative soils belonging to Aridisols of western Rajasthan, and differing in physico-chemical pruperties, were studied for P adsorption characteristics. The data followed Langmuir adsorption isotherms. Adsorption maxima (b) varied from 0.078 to 3.470 mg P per g soil and was significantly correlated with organic matter and cation exchange capacity (CEC) of the soils. However. bonding energy coefficient (K) vaiues varied from 0.016 to 0.215 llg mr I and showed no correlation with any soil property. The phosphorus buffering capacity (PBC) varied from 1.45 to 11.76 ml got soil. Non-calcareous soils have higher PBC than calcareous soils. The per cent phosphate adsorption was found related with bonding energy. The finding suggests that P requirement of arid soils with low clay content and organic matter mainly depend on PBC and CaC03 content of the soils.